Struktur Kebahasaan Bahasa Indonesia sebagai Rujukan Penggunaan Bahasa (Morfologi) - Muhammad Faisal; Rahma Ashari Hamzah; Afdal Syahreza (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This article discusses the linguistic structure of Indonesian with an emphasis on the importance of morphology as one of the main aspects in learning and understanding language. Morphology, as a branch of linguistics, studies the internal structure of words and the process of their formation through affixation, reduplication, and composition. This study aims to analyze the types of morphemes—including free, bound, derivational, and inflectional morphemes—and to understand the morphological process and grammatical classes in Indonesian systematically. Through this study, it is also explained how affixation (prefix, suffix, infix, and confix), reduplication in various forms, and compound word composition play a role in forming meaning. This study highlights the importance of morphology in language teaching, communication, and development, and emphasizes that understanding morphological structure will improve language skills accurately and effectively, both in formal and informal contexts, and strengthen the sense of familiarity and awareness of the richness of Indonesian.